2017
DOI: 10.1525/abt.2017.79.2.81
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Use of Evolutionary Trees (MUET) to Inform K-14 Biology Education

Abstract: Evolutionary trees are powerful tools used in modern biological research, and commonly used in textbooks and classroom instruction. Studies have shown that K-14 students have difficulties interpreting evolutionary trees. To improve student learning about this topic, it is essential to teach them how to understand and use trees like professional biologists. Unfortunately, few currently used teaching frameworks for evolution instruction are designed for this purpose. In this study we developed the Model of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This model has previously been successfully applied to the identification of visual competencies in biochemistry learning ( Schönborn and Anderson, 2009 , 2010 ), the structuring of verb–noun reasoning statements, and the design of assessments of student reasoning and problem-solving abilities ( Anderson et al , 2013 ). In addition, the CRM model has been used to guide research looking at how scientists use evolutionary trees ( Kong et al , 2017 ) and how they explain molecular and cellular mechanisms ( Trujillo et al , 2015 ) and, together with the assessment triangle ( NRC, 2001 ), to guide the development of assessment instruments ( Dasgupta et al , 2016 ). The CRM model offers a useful way to account for all the concepts (C), types or modes (M) of representations, and ways of reasoning (R) with those concepts (RC) and representations (RM; Schönborn and Anderson, 2009 , 2010 ).…”
Section: How To Apply the Five Steps Of Picuramentioning
confidence: 99%
“…This model has previously been successfully applied to the identification of visual competencies in biochemistry learning ( Schönborn and Anderson, 2009 , 2010 ), the structuring of verb–noun reasoning statements, and the design of assessments of student reasoning and problem-solving abilities ( Anderson et al , 2013 ). In addition, the CRM model has been used to guide research looking at how scientists use evolutionary trees ( Kong et al , 2017 ) and how they explain molecular and cellular mechanisms ( Trujillo et al , 2015 ) and, together with the assessment triangle ( NRC, 2001 ), to guide the development of assessment instruments ( Dasgupta et al , 2016 ). The CRM model offers a useful way to account for all the concepts (C), types or modes (M) of representations, and ways of reasoning (R) with those concepts (RC) and representations (RM; Schönborn and Anderson, 2009 , 2010 ).…”
Section: How To Apply the Five Steps Of Picuramentioning
confidence: 99%
“…We developed a process for instructors to build customizable inductive curricular modules that can be used for teaching about and assessing understanding of relationships among taxa on a phylogeny, a key tree-thinking skill (Baum et al 2005;Novick and Catley 2013). Phylogenies are common in scientific publications (Catley and Novick 2008;Kong et al 2017) yet they are not constructed for the purpose of tree-thinking pedagogy therefore information in these published phylogenies can be difficult for students to extract and understand. The process we present demonstrates how to modify published phylogenies to use as teaching and assessment tools while retaining the fundamental information, evolutionary relationships among taxa, from the phylogenies.…”
Section: Tree-thinkingmentioning
confidence: 99%
“…To demonstrate how to modify published phylogenies to construct questions that require students to evaluate evolutionary relationships among taxa on evolutionary trees, we show an initial phylogeny ( Fig. 1a) that depicts the evolutionary relationships of the taxa as might be seen in a scientific publication (Catley and Novick 2008;Kong et al 2017). Next, by rotating clades at internal nodes ( Fig.…”
Section: Common Incorrect Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that experience with real scientific data and professional research will help students master computational reasoning and tree-thinking (Kong et al, 2017). While that is certainly true, we present a complementary perspective here, using “right-brain” storytelling and images to engage students in evolutionary thinking, phylogenies, and computational biology concepts.…”
Section: Introductionmentioning
confidence: 99%